Experimental program on mechanical properties of large rock fractures. Issue 1 (August 2021) - Jacobsson, L; Ivars, D Mas; Kasani, H A; Johansson, F; Lam, T
Abstract: Predictions of fracture displacements are required to support the safety assessments of a deep geological repository for nuclear spent fuel. Laboratory and in-situ experiments are used to estimate these properties. Despite significant contributions in the last decades, there is a knowledge gap in terms of the impact of high normal stresses on the mechanical properties of large-scale fractures under Constant Normal Stiffness (CNS) boundary conditions. Within the framework of the POST project, a cooperative effort was made by SKB (Sweden), NWMO (Canada), and Posiva from Finland (in phase 1) to study these questions. In the second phase of the POST project, a first of a kind direct shear testing machine was manufactured and calibrated that can accommodate samples up to 400 × 600 mm under normal stresses up to 10 MPa, for both CNS and Constant Normal Load (CNL) conditions, with the ability to shear the sample up to 50 mm. Several best practice procedures were developed for fracture characterization pre-, syn-, and post-shear test which utilize high resolution optical scanning, contact pressure measurements, Digital Image Correlation (DIC) measurements, and acoustic emission measurements during the shear test. Natural and tensile-induced fractures of a granitic rock as well as replicas of the hard rock fractures, at three different fracture sizes of 35×60 mm, 70×100 mm, and 300×500 mm, are now being tested. It is hoped that this program will provide a set of high-quality data which will help reduce the knowledge gap in the understanding of fracture behavior.